A) x^2-(x+3)(x-3)=3x

6) 4x^2 - 9 = 0
решить

Raf4ik15 Raf4ik15    1   22.01.2021 12:58    1

Ответы
KitBanin KitBanin  22.01.2021 13:00

Объяснение:

a) x²-(x+3)(x-3)=3x     (это разность квадратов)

x² - (x²-9) = 3х

x²-x²+9 = 3х     (сокращаем)

3х = 9

х = 3

6) 4x² - 9 = 0       (это разность квадратов)

(2х)²-3² = 0

(2х-3)(2х+3) = 0     (произведение равно 0,когдаодин измножителей равен 0)

2х-3 = 0              или       2х+3 = 0

2х = 3                               2х = -3

х₁ = 1,5                               х₂ = -1,5

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра